Tarjamah Ayat-Ayat Al-Quran dengan Tembang Macapat dalam Wayang Kekayon Khalifah Yogyakarta - Lutfianto, Lutfianto (JURNAL AT-TURAS, 2020)
The Qur'an is kalamullah which contains great teachings and is conveyed in beautiful Arabic. This beauty can be approached by the beauty of the local language. For example in Java, the beauty of language in the Qur'an can also be felt when translated with a literary approach. One of them is literature that developed in Java, namely the art of song macapat. This macapat song art is used in the performance of Wayang Kekayon Khalifah Yogyakarta when translating the Qur'an. The author wants to present the translation of the Qur'an with macapat song that is in Wayang Kekayon Khalifah Yogyakarta. Macapat song in question is masumambang and pangkur. It aims to help readers understand the translation of the Qur'an with macapat song. The results showed that the translation of the Qur'an with the song of macapat presents the beauty and nuances of regionalism. Puppet Kekayon Khalifah Yogyakarta which presents a translation of the Qur'an with the song of macapat gives a new color to the universe of wayang. So that the Qur'an as a source of Islamic teachings can be delivered with wisdom.Keywords:  Wayang Kekayon Khalifah Yogyakarta, Al-Qur’an Translation, and Tembang Macapat